Pentingnya Pendidikan Karakter Pada Anak Sekolah Dasar di Era Serba Digital - kirana mustofa, inayah dian (Maliki Interdisciplinary Journal, 2025)
Character education for elementary school children is an important aspect in shaping a child's personality and morals from an early age. Amid the rapid development of digital technology, the challenges in educating a child's character have become increasingly complex. The digital era, with easy access to information through the internet, social media, and other technological devices, has a significant impact on children's mindset and behavior. Therefore, character education must be in line with technological developments, utilizing the potential of technology to support the formation of good moral, ethical, and social values. Instilling values such as honesty, responsibility, discipline, cooperation, and empathy is crucial during elementary school age, as this is a critical period in the formation of a child's character. Furthermore, supervision in the use of technology and wise guidance are necessary to avoid negative impacts that could harm the child's social and emotional development. This article aims to explain the importance of character education for elementary school children in the digital era and how character education can be carried out alongside technological advancements to shape a generation that is not only academically intelligent but also possesses strong character and noble values.